Project-Based Learning (PjBL) in teaching writing and presentation skills: An analysis within the Kurikulum Merdeka - Hoirul Ummah; Joko Priyana; Ilma Zahriyatun Nadhiroh; Wanda Hamida; Handayani Handayani; Diana Indah Fitriyah (English Learning Innovation, 2026)
Project-Based Learning (PjBL) has gained growing recognition as an effective approach in language teaching and learning. However, its application in developing students’ writing and presentation skills remains underexplored, particularly within the implementation of Kurikulum Merdeka in Indonesia, which emphasizes 21st-century skills. This research aims to explore the stages in implementing PjBL to teach writing and presentation skills in K-12 learners in Indonesia. This study employed a qualitative descriptive design. The participant of this research is an English teacher who actively implemented PjBL in the classroom. In collecting data, researchers used observation, in-depth interviews, and document review, including lesson plans, modules, and syllabi. Then, the data were analyzed using thematic analysis to clarify detailed information, and the technique of triangulation was employed as a means of ensuring the trustworthiness of the data. The findings revealed three primary stages of PjBL implementation in teaching writing and presentation skills: planning, implementation, and reporting stages. Planning stages include determining the project topic, conducting preliminary activities, formulating key questions, drafting project plans, and creating a project timeline. Then, the implementation stages included finishing the project. Lastly, the reporting stages were completed, which included assessing the project’s results and evaluating its progress. These findings highlight how PjBL can be systematically structured to address practical challenges in teaching writing and presentation skills, while supporting the broader objective of Kurikulum Merdeka.